Pardon's Judicial Urgency in Renewing Criminal Law in Indonesia - Satria Fajar Putra Dipayana; Eva Achjani Zulfa (LEGAL BRIEF, 2022)
This paper will examine the concept of judicial pardon (forgiving judges) as a solution to the existing legal problems, which are perceived as an attempt to avoid incarceration. The law gives the judge the authority to forgive or pardon the convict without imposing a crime or action if they are influenced by certain factors. This article aims to convey the importance of the RKUHP's concept of judicial pardon to the future renewal of the criminal justice system. This article's research employs a normative, statutory, and conceptual approach to the law. The findings of this study indicate that the concept of judicial pardon can be viewed as the final gatekeeper for a case that disrupts social justice, or as a guide for the forgiveness of judges that functions as a safety valve or emergency door. Then in accordance with the noble values that exist in Indonesian society, such as those of the people of Jambi province, the Batak Karo, the Balinese, and many others. In order for future generations of Indonesians to realize the welfare and protection of the community, as a form of legal certainty in sentence execution.